PENGEMBANGAN ALAT PERMAINAN EDUKATIF MAZE BOX UNTUK MENSTIMULASI ASPEK KOGNITIF PADA ANAK USIA 5-6 TAHUN - Fithriyanti, Nurul; Efendi, Dwi Imam; Marli'ah, Siti (GCEJ (Golden Childhood Education Journal), 2023)
The purpose of this study is to develop educational game tools suitable for stimulating the cognitive aspects of children over the age of 56. This study is a developmental study inherited from Borg & Gall's 10-step R & D. The researchers performed only five steps: 1) possibilities and probllems, 2) data collectioan, 3) prodact desigen, 4) desigen verification, and 5) desigen improvement. The research tools used were observations, surveys, and documentation. Product feasibility is based on the results of evaluations by media and materials experts. The results of the evaluation by media experts receive an average score of 3.29 on a very good basis. The results of the material expert evaluation gave an average score of 2.92 on the corresponding criteria, so the entire product of the developed Maze Box educational game tool stimulates the cognitive aspects of children over the age of 56. Was considered suitable for.